Determine the Frequency of Different Causes CF Upper Gastrointestinal Bleed - Daud Ghilzai, Abdul Matin Qaisar, Ali Hyder Mugheri, Muhammad Irfan Rashed, Shahid Muneer, Abrar Shaikh, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of various causes for upper gastrointestinal bleed. Study Design: Observational study. Place and Duration of Study: Department of Gastroenterology, Bolan Medical College Quetta from 1st July 2021 to 31st March 2022. Methodology: One hundred and thirty five patients in an age limit of >30 years were registered. The inclusion criteria were based on clinical diagnosis of GB of upper tract, blood tests included H-pylori conformational test as well as CBC. The first endoscopy was performed within the 48 hours initiation of bleeding. Results: The mean was 41.2±4.5 years. There were 68.8% males and 31.1% females. The main cause of gastrointestinal bleeding in cases was observed as varices and gastric ulcers highest within 40-60 years group while erosive gastritis and duodenal ulcers were presented most in males. Conclusion: The frequency of varices was 65.9% followed by 10.37% gastric ulcers presented in gastrointestinal bleeding of upper tract. Keywords: Gastrointestinal bleeding, Varices, Melena